Diuretic Enhanced Ultrasonography in the Diagnosis of Pyeloureteral Obstruction - Vytis Kazlauskas; Andrius Cekuolis; Vytautas Bilius; Marius Anglickis; Gilvydas Verkauskas (Medicina, 2019)
Background and Objectives: To determine the value of diuretic ultrasonography for the diagnosis of obstructive hydronephrosis. Materials and Methods: Diuretic enhanced ultrasonography was used routinely as a part of examination of patients with hydronephrosis in our Department. There were 72 patients (42 males, 30 females; aged 2 months to 17 years; median age 7.07 years) with a sonoscopic diagnosis of hydronephrosis included from January 2006 until October 2011. The anteroposterior diameter (AD) of renal pelvis was measured sonoscopically before and at sixty minutes after furosemide injection. A weight-adjusted dose of 1 mg/kg of furosemide was administered intravenously. Results: Patients were operated on if pyeloureteral obstruction was suspected because of low or deteriorating differential renal function, increasing hydronephrosis or symptoms thereof. Hydronephrosis was unilateral in 61 (84.7%) and bilateral in 11 (15.3%) patients. The median AD of pelvis before furosemide injection was 22 mm in operated and 17 mm in non-operated patients (p = 0.005). Sixty minutes after furosemide injection, the AD of pelvis in operated patients was 35.5 mm and 25.8 mm in non-operated—25.8 mm (p < 0.001). Logistic regression model demonstrated that significant factors for surgery were: AD 60 min after furosemide infection and ultrasonographic parenchymal sclerosis. Conclusion: Ultrasound measurement of the AD of renal pelvis 1 h after the injection of furosemide used as an additional investigation can help in predicting obstructive hydronephrosis.